The Effect Of Net Profit, Dividend Payout Ratio, And Liquidity On Stock Price (Healthcare Companies Listed on the Indonesia Stock Exchange, 2021–2024) - Muhammad Iqbal Annazhari; Sudarwati; Fithri Setya Marwati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This research examines how net profit, dividend payout ratio (DPR), and liquidity influence the share prices of healthcare firms listed on the Indonesia Stock Exchange (IDX) between 2021 and 2024. Employing a quantitative descriptive methodology, the study utilized secondary sources, including financial statements and annual reports, from a purposive sample of 10 healthcare companies, resulting in 40 data points. Net profit was defined as post-tax earnings, DPR as the percentage of net profit allocated to dividends, liquidity via the current ratio, and stock price according to closing market values. Data analysis involved testing classical assumptions, followed by multiple linear regression, with t-tests, F-tests, and R² applied to evaluate the model’s explanatory capacity. Findings indicate that both net profit and DPR exert a significant negative impact on stock prices, whereas liquidity demonstrates a positive and significant effect. These results imply that investors may approach high profits or dividend distributions with caution, potentially due to perceived limitations on growth or innovation, while robust liquidity conveys financial stability and bolsters investor confidence. Overall, liquidity stands out as a primary factor driving stock price movements in the healthcare sector during the post-pandemic adjustment phase.